Constructive heuristic algorithm in branch-and-bound structure applied to transmission network expansion planning - Romero, R.; Asada, E. N.; Carreno, E.; Rocha, C. (Institution Engineering Technology-iet, 2007)
A constructive heuristic algorithm to solve the transmission system expansion planning problem is proposed with the aim of circumventing some critical problems of classical heuristic algorithms that employ relaxed mathematical models to calculate a sensitivity index that guides the circuit additions. The proposed heuristic algorithm is in a branch-and-bound algorithm structure, which can be used with any planning model, such as Transportation model, DC model, AC model or Hybrid models. Tests of the proposed algorithm are presented on real Brazilian systems.